2011
DOI: 10.1186/1556-276x-6-137
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic nanotubes reinforced polyvinylidene fluoride composites as low-cost electromagnetic interference shielding materials

Abstract: Novel polymer nanocomposites comprising of MnO2 nanotubes (MNTs), functionalized multiwalled carbon nanotubes (f-MWCNTs), and polyvinylidene fluoride (PVDF) were synthesized. Homogeneous distribution of f-MWCNTs and MNTs in PVDF matrix were confirmed by field emission scanning electron microscopy. Electrical conductivity measurements were performed on these polymer composites using four probe technique. The addition of 2 wt.% of MNTs (2 wt.%, f-MWCNTs) to PVDF matrix results in an increase in the electrical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(60 citation statements)
references
References 33 publications
1
59
0
Order By: Relevance
“…In this regard, polymer-matrix composites containing conductive fillers are attractive for shielding due to their processability and low density. Literature studies have been focused on filler's reinforced on thermoplastic polymer composites such as poly(methyl methacrylate) (PMMA) [25,26] , polypropylene (PP) [27] , polyvinylidene fluoride (PVDF) [28,29] , polyacrylate [30] , cellulose triacetate [31] , ethylene vinyl acetate (EVA) [32] , reactive ethylene tetrapolymer (RET) [33] , polycarbonate (PC) [34] and Poly (vinyl alcohol) (PVA) [35] are commonly used as polymer matrix due to flexible molecular chains, high strength and its ductile nature. In order to increase the EMI shielding efficiency, nanofillers doped into polymer matrix should be conducting / magnetic in nature.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, polymer-matrix composites containing conductive fillers are attractive for shielding due to their processability and low density. Literature studies have been focused on filler's reinforced on thermoplastic polymer composites such as poly(methyl methacrylate) (PMMA) [25,26] , polypropylene (PP) [27] , polyvinylidene fluoride (PVDF) [28,29] , polyacrylate [30] , cellulose triacetate [31] , ethylene vinyl acetate (EVA) [32] , reactive ethylene tetrapolymer (RET) [33] , polycarbonate (PC) [34] and Poly (vinyl alcohol) (PVA) [35] are commonly used as polymer matrix due to flexible molecular chains, high strength and its ductile nature. In order to increase the EMI shielding efficiency, nanofillers doped into polymer matrix should be conducting / magnetic in nature.…”
Section: Introductionmentioning
confidence: 99%
“…11 However, they suffer from poor chemical resistance, corrosion, high density and difficulty in processing. 3,[12][13][14][15][16][17][18][19]28 Above electrical percolation threshold (PT), CNTs impart conductivity by creating a three dimensional interconnecting network in polymer matrix. Amongst various carbon based conducting composites; viz., carbon nanotubes (CNTs), 3,[12][13][14][15][16][17][18][19] graphite, 20 carbon black, [21][22][23] carbon fibres 24,25 and graphenes, 26,27 CNT composites have shown promising EMI shielding properties due to their good electrical properties and large aspect ratio.…”
mentioning
confidence: 99%
“…Polymer composites with carbon based fillers could be potential replacements for conventional materials as EMI shielding materials due to their unique combination of light-weight and mechanical, electrical and thermal properties. 3,[12][13][14][15][17][18][19][20][28][29][30][31][32][33][34][35][36][37][38][39] Here we present a brief overview of some important studies reported on polymer based composites for EMI shielding applications. 3,[12][13][14][15][16][17][18][19]28 Above electrical percolation threshold (PT), CNTs impart conductivity by creating a three dimensional interconnecting network in polymer matrix.…”
mentioning
confidence: 99%
“…It is well known that there are three loss mechanisms to prevent electromagnetic wave from penetrating EMI shielding materials, i. e. the reflection loss, absorption loss and multiple reflection loss of the electromagnetic radiation [2]. Allowing for the increasing requirements of high shielding effectiveness (SE) and low reflection of electromagnetic wave to the surrounding environment in modern electronic industry, improving the absorption loss of materials is very favorable and it has attracted much attention to develop various microwave absorbents.…”
Section: Introductionmentioning
confidence: 99%